6d-2(d-2)=3(d-12)

Simple and best practice solution for 6d-2(d-2)=3(d-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6d-2(d-2)=3(d-12) equation:


Simplifying
6d + -2(d + -2) = 3(d + -12)

Reorder the terms:
6d + -2(-2 + d) = 3(d + -12)
6d + (-2 * -2 + d * -2) = 3(d + -12)
6d + (4 + -2d) = 3(d + -12)

Reorder the terms:
4 + 6d + -2d = 3(d + -12)

Combine like terms: 6d + -2d = 4d
4 + 4d = 3(d + -12)

Reorder the terms:
4 + 4d = 3(-12 + d)
4 + 4d = (-12 * 3 + d * 3)
4 + 4d = (-36 + 3d)

Solving
4 + 4d = -36 + 3d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-3d' to each side of the equation.
4 + 4d + -3d = -36 + 3d + -3d

Combine like terms: 4d + -3d = 1d
4 + 1d = -36 + 3d + -3d

Combine like terms: 3d + -3d = 0
4 + 1d = -36 + 0
4 + 1d = -36

Add '-4' to each side of the equation.
4 + -4 + 1d = -36 + -4

Combine like terms: 4 + -4 = 0
0 + 1d = -36 + -4
1d = -36 + -4

Combine like terms: -36 + -4 = -40
1d = -40

Divide each side by '1'.
d = -40

Simplifying
d = -40

See similar equations:

| (x+7)(2x^2-6x-2)= | | 5b-3=7b+11 | | 4x+10y=35 | | x(5-x)+4(x^1)= | | (5x-6)(4x-7)= | | (5x-7)(3x-2)= | | -7=12-k | | 4d-3=21 | | -32=x-17 | | 237x^2-56x= | | 8x^5y(9x^2+x^2y^3-8y^4)= | | 5a+13=7e-21 | | 3x^2-19x=63 | | 7y-5y=6 | | (4x-5)+(3x-1)= | | (4x^6)(-2x^5)(3x^9)= | | 24.2-18.5P=6.6P-1.9(9P+2) | | 12=k-2+6k | | (-x^2+3x)+(2x^2+7)+(5x-2)= | | 806-?=368 | | z-4=5 | | q+2=3 | | 5x-8x-7= | | 6m+5n-3m+11n= | | 2p^8+5p^4q-12q^2= | | q+.33=.5 | | (5x^2+4x-8)+(3x^2+3x+14)-(8x^2-11)= | | -14y^2-9y^2+12y^2+61xy^2-18xy^2= | | -28-2.6q=-3.8q+4(4.3q+1) | | (3x^2+2x-3)+(5x^2+4x+13)-(8x^2-18)= | | -.7q-(-4+0.9q)=2.8 | | 3.2-9x+7.1-3x=0 |

Equations solver categories